Dari Limbah Kain Perca Menjadi Rupiah: Kolaborasi Kreatif dengan Bank Sampah di Desa Karangmojo Kabupaten Sukoharjo - Nuria Amanah, Aisah; Dini Dwi Puspita; Abdul Jabbar (Jurnal Bina Desa, 2025)
Rag waste, left over from textile production, poses a serious environmental problem in Indonesia due to its difficulty in decomposing and its often-perceived lack of value. In an effort to address this issue, the UNNES Giat 9 team conducted a community service program in Karangmojo Village, Sukoharjo Regency, aimed at transforming rag waste into economically valuable products. This initiative involved the waste bank community "Dadi Makmur" through socialization and training in making doormats from patchwork waste. The training not only improved the community's skills in waste processing but also successfully opened new business opportunities, evidenced by the sale of 7 out of the 10 mats produced during the program. This program also supports the concept of a circular economy by reducing waste and maximizing the reuse of existing resources. The results of this activity demonstrate that the utilization of patchwork waste has great potential to improve the economic welfare of the community while contributing to environmental sustainability. This success is expected to inspire other communities to undertake similar initiatives in efforts to create a cleaner and healthier environment while increasing income through the effective utilization of previously underutilized waste.